Perlindungan Hukum Netflix Atas Penjualan Akun Premium Di Media Sosial - Latulola, Veldha Arabella; Kuahaty, Sarah Selfina; Pesulima, Theresia Louize (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2024)
Introduction: Netflix application as a copyrighted work that is protected in Law Number 28 of 2014 concerning Copyright. Article 9 Paragraph (1) point b and e regulates that the duplication of creation in all its forms and the distribution of creation or copies thereof are the rights of the creator, but in the development of the digital world today Netflix premium accounts are often offered not by Netflix for sale. Purposes of the Research: Analyze Netflix's legal protection of selling premium accounts on social media. Methods of the Research: The research method used is Normative Juridical, the research approach uses a statutory approach and a conceptual approach. The source of legal materials is in the form of premier legal materials, secondary legal materials and tertiary legal materials. The technique of collecting legal materials in this study through literature studies, then analyzed qualitatively. Results of the Research: As a result of this research, the sale of Netflix premium accounts through social media is an infringement of copyright. The form of legal protection that can be taken by Netflix is in the form of preventive legal protection and repressive legal protection. Preventive legal protection is contained in Article 54 of Law Number 28 of 2014 concerning Copyright and in the form of a complaint column on the Netflix website for reporting copyright infringement provided by the Netflix Application. Meanwhile, repressive legal protection is contained in Article 55 of Law Number 28 of 2014 concerning Copyright. Legal efforts taken by the Netflix application with the settlement of litigation in the form of a lawsuit for compensation and a report on the closure of content or rights.